99m-technetium-labeled red blood cells' single-photon emission computed tomography/computed tomography in situs ambiguous with polysplenia - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Situs ambiguous or heterotaxy syndrome is defined as the abnormal arrangement of organs and vessels within the body. Herein, we present an 8-year-old girl with growing right-sided suprarenal masses mimicking adrenal tumors. Technetium-99-m-radiolabeled red blood cells' planar images were inconclusive for the diagnosis of splenic tissue in the right side. Single-photon emission computed tomography/computed tomography imaging clearly identified right-sided functioning spleens and confirmed the diagnosis of situs ambiguous with polysplenia.
Keywords: Heterotaxy syndrome; polysplenia; selective spleen scintigraphy; single-photon emission computed tomography; computed tomography; situs ambiguous; technetium-99m-labeled red blood cells; SPLEEN